Minimizing wear of EDM electrode in machining a hard material - Muhammad Qahri Harir, Mohd Rapi (2017)
Electrical discharge machining (EDM) is extremely being used in manufacture of aerospace and automotive parts, also used in development of dies and molds by machining and cut the materials that are strong and hard, which impossible to be machined by traditional machining techniques. However, the main problem of EDM is electrode wear which is mainly caused by debris. In this present study, three types of electrode designs were developed for comparison. The electrode with magnet is used to pull the debris and avoid it from accumulates at the bottom of machined area. Holes also being made at the electrode to improve the flows of debris so that it can be pulled straight away to the magnet inside the electrode. Video measuring system will helps in viewing the zoomed image of electrode so that the wear can be see clearer. Also, electronic balance is used to weigh the weight of electrode to know the amount of electrode wear. Finding from this project show that the electrode with magnet and holes will be more helpful in minimizing the wear of the EDM electrode compared to others.